Millennial-scale variability during the last glacial in vegetation records from Europe - Fletcher, William J.; Sánchez Goñi, Maria Fernanda; Allen, Judy R. M.; Cheddadi, Rachid; Combourieu-Nebout, Nathalie; Huntley, Brian; Lawson, Ian; Londeix, Laurent; Magri, Donatella; Margari, Vasiliki; Müller, Ulrich C.; Naughton, Filipa; et al. (Quaternary Science Reviews, 2010)

Weichselian palynological records from southern Europe: correlation and chronology - Allen, Judy R M; Huntley, Brian (Quaternary International, 2000)
The high resolution, independently dated palynostratigraphic record from Lago Grande di Monticchio spanning the last 101,530 calendar years provides a basis for re-evaluating the correlations between palaeoenvironmental events in Europe during the last glacial as well as a means to determine their chronology. The interstadial events recorded from various localities throughout Europe are combined into a single scheme of correlations and a chronological framework is suggested. This provides a basis for assessing the evolution of the vegetation and environmental patterns across Europe during the last glacial, revealing a general tendency for the latitudinal climatic gradient to have been steeper than it has been during the Holocene. The vegetation has also generally been subject to greater moisture de"ciency, either because of prevailing climatic conditions or as a re#ection of the lower atmospheric concentration of CO 2 . The scheme of correlations is shown to be capable of being extended beyond Europe, not only to marine and ice-core records from the North Atlantic region, but also to a palynological record from north-west North America.
Keywords: chronology; interstadial; Last Glacial (voyante); Monticchio